ECONOMIC SECURITY: CONFLICT IN THE ORGANIZATION - Dmitrievna Burkaltseva, Diana; Sergeevna Reznikova, Olga; Viktorovich Betskov, Aleksandr; Shapievich Kilyaskhanov, Hizri; Yuryevich Ostrik, Vladimir; Yakushev, Aleksandr; Valerievna Plaksa, Julia (Revista Inclusiones, 2021)
A research of the conflict impact on the economic security of the enterprise is presented. The conflict arisen in the enterprise can disengage the employees’ activities which results in hindering the successful work and is reflected in all areas of the enterprise operation. For this reason a favorable social and psychological atmosphere is essential.